2022
DOI: 10.3389/fpls.2022.1085395
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and transcriptome profiling revealed defense networks during Cladosporium fulvum and tomato interaction at the early stage

Abstract: Tomato leaf mold caused by Cladosporium fulvum (C. fulvum) is a serious fungal disease which results in huge yield losses in tomato cultivation worldwide. In our study, we discovered that ROS (reactive oxygen species) burst was triggered by C. fulvum treatment in tomato leaves. RNA-sequencing was used to identify differentially expressed genes (DEGs) induced by C. fulvum inoculation at the early stage of invasion in susceptible tomato plants. Gene ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…1 A). The Peptide Mass Fingerprint analysis of the tryptic peptides gave a significant match with peroxidase from Solanum lycopersicum and it was precisely recognized as the LePrx21 gene product, a suberization-associated anionic peroxidase 2-like (NCBI Reference Sequence: XP_004234138.1; UniProtKB accession A0A3Q7FFR5), which consisted of 334 amino acids and was implicated in the defence response to environmental stresses such as wounding, Mn excess 10 , pathogen attack or oxidative stress 11 , 12 . The total coverage of the protein sequence was 64% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 A). The Peptide Mass Fingerprint analysis of the tryptic peptides gave a significant match with peroxidase from Solanum lycopersicum and it was precisely recognized as the LePrx21 gene product, a suberization-associated anionic peroxidase 2-like (NCBI Reference Sequence: XP_004234138.1; UniProtKB accession A0A3Q7FFR5), which consisted of 334 amino acids and was implicated in the defence response to environmental stresses such as wounding, Mn excess 10 , pathogen attack or oxidative stress 11 , 12 . The total coverage of the protein sequence was 64% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With advancements in next-generation sequencing, RNA-Seq has become an important means for researchers to study the mechanism of plant disease resistance. Through physiological index determination and transcriptome sequencing, Peng et al (2022) showed that the expression of multiple core defense genes involved in fungal disease resistance and hormone signaling pathways is induced in tomato (Solanum lycopersicum) upon Cladosporium fulvum infection. Wei et al (2022) sequenced the transcriptome of Amorphophallus spp.…”
Section: Discussionmentioning
confidence: 99%